Epidemiology of invasive fungal infections during induction therapy in adults with acute lymphoblastic leukemia: a GRAALL-2005 study. Issue 3 (4th March 2017) - Mariette, Clara; Tavernier, Emmanuelle; Hocquet, Didier; Huynh, Anne; Isnard, Françoise; Legrand, Faezeh; Lhéritier, Véronique; Raffoux, Emmanuel; Dombret, Hervé; Ifrah, Norbert; Cahn, Jean-Yves; Thiébaut, Anne
Abstract: Little data have been published concerning invasive fungal infections during treatment of acute lymphoblastic leukemia (ALL). Patients included between May 2006 and October 2012 in the multicenter phase III trial for newly diagnosed ALL (GRAALL-2005) were retrospectively reviewed for the occurrence of IFI using the EORTC modified criteria. These patients did not routinely receive antifungal prophylaxis. Among 969 patients included (median age 47 years), 65 (6.7%) developed IFI during induction chemotherapy: 26 (3.3%) invasive aspergillosis (IA), 33 (3.4%) invasive candidiasis (IC) and six other IFI. For IA, the median time between induction therapy and IA diagnosis was 20 days. Diagnosis was probable in 22 cases and proven in four. Aspergillus antigen in serum was tested in all cases and positive in 24. Overall 12-week mortality after diagnosis of IA was 5/26 and attributable mortality related to the infection was 4/26 (15.4%). For IC, the median time between induction therapy and diagnosis was 19 days. Diagnosis was proven in 29 episodes. Candida albicans was the major pathogen in yeast infections (16/27). Overall 12-week mortality after diagnosis of IC was 8/33 (24.2%) and attributable mortality related to the infection was 7/33. The median delay between induction chemotherapy initiation and attributable death related to IC was 15 days. These findings may help to optimize the future management of ALL patients, and as in AML advocate systematic monitoring and the development of prophylactic or preemptive antifungal treatments.